VD_FINDINFO Décision / 2014 / 243 vom 13. März 2014 - VD Tribunal cantonal (2014)
DÉTENTION POUR DES MOTIFS DE SÛRETÉ, RISQUE DE RÉCIDIVE | 221 al. 1 let. c CPP (CH), 227 al. 7 CPP (CH), 229 al. 3 let. b CPP (CH)